Unraveling SREBF1’s role in elevating colorectal cancer prognosis through proliferation and migration inhibition - Dongling Li; Qinrui Cai; Fan Xu; Ling Lin; Xiaoya Zhou; Li Li; Yao Chen; Tianlin Feng; Yuanxiu Gan; Chenhua Zhang; Fan Yang (PLoS ONE, 2025)
Sterol Regulatory Element-Binding Protein 1 (SREBF1), a central regulator of lipid metabolism, has unclear pan-cancer roles and clinical implications. This study integrated various databases and functional experiments to systematically investigate the heterogeneous characteristics of SREBF1 across cancers. Pan-cancer analysis revealed significant upregulation of SREBF1 in multiple cancer types, including colorectal cancer (CRC). Survival analysis demonstrated that SREBF1 overexpression serves as an independent risk factor for poor prognosis in colorectal cancer patients. Focusing on CRC, functional studies revealed that SREBF1 drives tumor progression by enhancing cancer cell proliferation and migration, while its knockdown induces cell cycle arrest and apoptosis in HCT116 cells. Mechanistically, SREBF1 is implicated in lipid metabolic reprogramming and interacts with the tumor immune microenvironment, also with genetic alterations. This study highlights the regulatory role of SREBF1 in pan-cancer contexts and provides novel insights into its potential as a prognostic biomarker and therapeutic target, particularly in colorectal cancer.